2010
DOI: 10.1128/mcb.00038-09
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Phosphate Phosphatase 3 Stabilization of β-Catenin Induces Endothelial Cell Migration and Formation of Branching Point Structures

Abstract: Endothelial cell (EC) migration, cell-cell adhesion, and the formation of branching point structures are considered hallmarks of angiogenesis; however, the underlying mechanisms of these processes are not well understood. Lipid phosphate phosphatase 3 (LPP3) is a recently described p120-catenin-associated integrin ligand localized in adherens junctions (AJs) of ECs. Here, we tested the hypothesis that LPP3 stimulates ␤-catenin/lymphoid enhancer binding factor 1 (␤-catenin/LEF-1) to induce EC migration and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 47 publications
2
61
0
Order By: Relevance
“…This was consistent with different functions that have been attributed for PPAP2B in ECs and SMCs. In ECs, PPAP2B localizes to adherens junctions and regulates ␤ -catenin signaling, thereby affecting cell migration ( 34 ). In SMCs, it regulates lysophospholipid signaling responses and affects SMC phenotypic plasticity ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with different functions that have been attributed for PPAP2B in ECs and SMCs. In ECs, PPAP2B localizes to adherens junctions and regulates ␤ -catenin signaling, thereby affecting cell migration ( 34 ). In SMCs, it regulates lysophospholipid signaling responses and affects SMC phenotypic plasticity ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mammalian LPPs have been demonstrated to localize to specific plasma membrane domains. Human (h) LPP1 (PPAP2A -Human Genome Nomenclature Committee) sorts apically, whereas hLPP3 colocalizes with Ecadherin in Madin-Darby canine kidney (MDCK) cells (Jia et al, 2003) and the C-terminal domain of hLPP3 has been shown to bind the AJ protein p120 catenin (catenin 1) (Humtsoe et al, 2010). However, it remains to be confirmed whether specific Wun-GFP localization is crucial for activity.…”
Section: Discussionmentioning
confidence: 99%
“…Catalytically dead forms of mammalian LPP3 can have effects on cells (Escalante-Alcalde et al, 2003;Humtsoe et al, 2010); therefore, we asked whether catalytic activity is required to rescue the tracheal defects. A mutant form of Wun2 in which a predicted catalytic histidine has been converted to lysine, H326K, is incapable of affecting the survival or migration of germ cells and shows no activity in vitro against PA (Starz-Gaiano et al, 2001;Renault et al, 2004).…”
Section: Lpp Activity Is Required Autonomously In Tracheal Cellsmentioning
confidence: 99%
“…HUVECs were treated with either control virus or virus encoding KIF13B-specific shRNA and were tested in a TER system for cell migration. (B) VEGF-mediated migration of HUVECs was determined by using the scratch wound healing assay (Humtsoe et al, 2010). HUVECs were treated with scrambled control siRNA or KIF13B-specific siRNA and were subjected to the scratch wound healing assay in the presence of 2.2 nmol/l VEGF.…”
Section: Impaired Kif13b Motor Function Shunts Vegfr2 To Lysosomesmentioning
confidence: 99%
“…In vitro capillary network formation on Matrigel (BD Biosciences, San Jose, CA) was performed as described previously (Humtsoe et al, 2010).…”
Section: Formation Of Capillary Network Structures In Vitromentioning
confidence: 99%